In Vitro Characterization of AtsB, a Radical SAM Formylglycine-Generating Enzyme That Contains Three [4Fe-4S] Clusters - Grove, Tyler L. (2008)
Sulfatases catalyze the cleavage of a variety of cellular sulfate esters via a novel mechanism that requires the action of a protein-derived formylglycine cofactor. Formation of the cofactor is catalyzed by an accessory protein and involves the two-electron oxidation of a specific cysteinyl or seryl residue on the relevant sulfatase. Although some sulfatases undergo maturation via mechanisms in which oxygen serves as an electron acceptor, AtsB, the maturase from Klebsiella pneumoniae, catalyzes the oxidation of Ser72 on AtsA, its cognate sulfatase, via an oxygen-independent mechanism. Moreover, it does not make use of pyridine or flavin nucleotide cofactors as direct electron acceptors. In fact, AtsB has been shown to be a member of the radical S-adenosylmethionine superfamily of proteins, suggesting that it catalyzes this oxidation via an intermediate 5′-deoxyadenosyl 5′-radical that is generated by a reductive cleavage of S-adenosyl-L-methionine. In contrast to AtsA, very little in vitro characterization of AtsB has been conducted. Herein we show that coexpression of the K. pneumoniae atsB gene with a plasmid that encodes genes that are known to be involved in iron–sulfur cluster biosynthesis yields soluble protein that can be characterized in vitro. The as-isolated protein contained 8.7 ± 0.4 irons and 12.2 ± 2.6 sulfides per polypeptide, which existed almost entirely in the [4Fe-4S](2+) configuration, as determined by Mössbauer spectroscopy, suggesting that it contained at least two of these clusters per polypeptide. Reconstitution of the as-isolated protein with additional iron and sulfide indicated the presence of 12.3 ± 0.2 irons and 9.9 ± 0.4 sulfides per polypeptide. Subsequent characterization of the reconstituted protein by Mössbauer spectroscopy indicated the presence of only [4Fe-4S] clusters, suggesting that reconstituted AtsB contains three per polypeptide. Consistent with this stoichiometry, an as-isolated AtsB triple variant containing Cys → Ala substitutions at each of the cysteines in its CX(3)CX(2)C radical SAM motif contained 7.3 ± 0.1 irons and 7.2 ± 0.2 sulfides per polypeptide while the reconstituted triple variant contained 7.7 ± 0.1 irons and 8.4 ± 0.4 sulfides per polypeptide, indicating that it was unable to incorporate an additional cluster. UV–visible and Mössbauer spectra of both samples indicated the presence of only [4Fe-4S] clusters. AtsB was capable of catalyzing multiple turnovers and exhibited a V(max)/[E(T)] of ~0.36 min(−1) for an 18-amino acid peptide substrate using dithionite to supply the requisite electron and a value of ~0.039 min(−1) for the same substrate using the physiologically relevant flavodoxin reducing system. Simultaneous quantification of formylglycine and 5′-deoxyadenosine as a function of time indicates an approximate 1:1 stoichiometry. Use of a peptide substrate in which the target serine is changed to cysteine also gives rise to turnover, supporting approximately 4-fold the activity of that observed with the natural substrate.